2021
DOI: 10.1002/oby.23139
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Internalized Weight Stigma During Pregnancy and Breastfeeding: A Prospective Longitudinal Study

Abstract: Objective This study aimed to examine the relationship between internalized weight stigma during pregnancy and breastfeeding outcomes at 1 month post partum among individuals with prepregnancy overweight or obesity. Secondarily, the study explored the temporal stability of internalized weight stigma from the third trimester to 1 month post partum via the Weight Bias Internalization Scale (WBIS). Methods A total of 103 pregnant individuals with overweight or obesity were recruited for this study. Participants c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Breastfeeding reduces the risk of respiratory diseases and diarrhea in infants and reduces infant mortality. Breastfeeding can also promote postpartum recovery, improve parent-child bond, and reduce the risk of diabetes, breast cancer, and ovarian cancer in mothers [ 3 ]. The World Health Organization and UNICEF recommend early initiation of breastfeeding and exclusive breastfeeding of infants under 6 months for optimal growth [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding reduces the risk of respiratory diseases and diarrhea in infants and reduces infant mortality. Breastfeeding can also promote postpartum recovery, improve parent-child bond, and reduce the risk of diabetes, breast cancer, and ovarian cancer in mothers [ 3 ]. The World Health Organization and UNICEF recommend early initiation of breastfeeding and exclusive breastfeeding of infants under 6 months for optimal growth [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The planned sample size was determined based on the findings of comparable surveys conducted in other countries [ 20 ]. With a confidence level (1 − α = 0.95), permissible error ( δ = 1.2) and response rate of the survey (95%), the required sample size was calculated to be 477 cases using PASS 11.0.…”
Section: Methodsmentioning
confidence: 99%
“…A US study of 358 postpartum women reported that almost one in five women ( n = 63) reported experiencing varying degrees of WS by providers in the medical setting [ 18 ]. A prospective longitudinal study in the US involving 103 women showed that the mean Weight Bias Internalization Scale (WBIS) score for postpartum women was 26.86 ± 13.03 (Scores range from 11 to 77) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Limited research, though, has examined internalization of weight stigma in pregnancy. One study found no association between internalization in the third trimester of pregnancy and eventual breastfeeding behavior 117 . However, the internalization scale was not pregnancy specific.…”
Section: The Wombs Frameworkmentioning
confidence: 98%